CHEMICAL AND METEOROLOGICAL INFLUENCES ON SURFACE OZONE DESTRUCTION AT BARROW, ALASKA, DURING SPRING 1989 - STURGES, WT; Schnell, R. C.; LANDSBERGER, S; OLTMANS, SJ; HARRIS, JM; Li, S. M. (ATMOSPHERIC ENVIRONMENT PART A-GENERAL TOPICS, 1993)
Surface ozone, particulate bromine and inorganic and organic gaseous bromine species were measured at Barrow, AK, during March and April 1989 to examine the causes of surface ozone destruction during the arctic spring. Satellite images of the Alaskan Arctic taken during the same period were also studied in conjunction with calculated air mass trajectories to Barrow to investigate the possible origins of the ozone-depleted air. It was found that during major ozone depletion events (O-3 < 25 ppbv) concentrations of particulate bromine and the organic brominated gases bromoform and dibromochloromethane were elevated. Air mass trajectories indicated that the air had crossed areas of the Arctic Ocean where leads had been observed by satellite. The transport time from the leads was typically a day or less, suggesting a fast loss mechanism for ozone. A similarly fast production of particulate bromine was shown by irradiating ambient nighttime air in a chamber with actinic radiation that approximated daylight conditions. Such rapid reactions are not in keeping with gas-phase photolysis of bromoform, but further studies showed evidence for a substantial fraction of organic bromine in the particulate phase; thus heterogeneous reactions may be important in ozone destruction.